2017
DOI: 10.1177/2156759x18772989
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors’ Emotional Intelligence and Its Relationship to Leadership

Abstract: In this investigation, we examined the relationship between emotional intelligence, leadership self-efficacy (LSE), self-leadership, and leadership experiences among a sample of practicing school counselors. School counselors who reported higher levels of emotional intelligence also reported greater LSE, self-leadership, and leadership experiences. We discuss the implications of these findings for the practice of school counseling and potential future research on school counselor leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 70 publications
5
9
1
2
Order By: Relevance
“…Specifically, our participants reported having the highest levels of EI for the subscale on managing their own emotions. Similarly, Mullen et al () found that practicing school counselors reported the ability to manage their emotions as the highest type of EI. This finding is notable because school counselors are encouraged to practice self‐care to prevent burnout (Mullen & Gutierrez, ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, our participants reported having the highest levels of EI for the subscale on managing their own emotions. Similarly, Mullen et al () found that practicing school counselors reported the ability to manage their emotions as the highest type of EI. This finding is notable because school counselors are encouraged to practice self‐care to prevent burnout (Mullen & Gutierrez, ).…”
Section: Discussionmentioning
confidence: 94%
“…Confirmatory factor analysis (CFA) of the WEIP‐S supported the four‐factor structure of the measure, scores on the WEIP‐S demonstrated test–retest stability through three time points, and scores on the WEIP‐S produced Cronbach's alpha ranging from .77 to .85 (Jordan & Lawrence, ). Mullen, Gutierrez, and Newhart () also found that in a sample of school counselors, Cronbach's alphas ranged from .80 to .89. In our study with school counselor trainees, scores on the WEIP‐S indicated acceptable internal consistency reliability, with Cronbach's alphas of .83 (awareness of own emotions), .72 (management of own emotions), .89 (awareness of others' emotions), and .88 (management of others' emotions).…”
Section: Methodsmentioning
confidence: 95%
“…The first section contains two evolving school counseling leadership models. In “School Counselors’ Emotional Intelligence and Its Relationship to Leadership Qualities,” Mullen, Gutierrez, and Newhart ( in press ) examine the relationship between emotional intelligence, leadership self-efficacy, self-leadership, and leadership experiences among a sample of practicing school counselors. Bowers, Lemberger-Truelove, and Brigman ( in press , in “A Social/Emotional Leadership Framework for School Counselors,” present social/emotional learning (SEL) as an effective intervention associated with personal growth, student achievement, and behavioral regulation.…”
Section: In This Issuementioning
confidence: 99%
“…That's assessment through sociometric assessments to find out social relationships between students who are involved in and outside the classroom [16,17]. Through information services, the School counselors can provide an understanding of how to manage emotional intelligence within oneself, develop social skills, and apply emotional intelligence skills to form a relationship with student peers/clique [18]. Therefore, the role of the school counselors in guiding students is very necessary, besides assisting students in providing Guidance and Counseling services, the school counselors can make observations about student development, in terms from the cognitive, affective, and psychomotor aspects of students [19].…”
Section: Introductionmentioning
confidence: 99%